The Ball Mill Driving Device Fault and the Main Bearing Lubrication Analysis - Tong Junfeng; Hou Honghai; Zhao Hongxia (Institute of Advanced Engineering and Science, 2013)
This article from the analysis of the power consumption of the ball mill and the work characteristic of the motor, analyzes the fault reason of ball mill transmission equipment. The paper mainly deals with a side-transmission ball mill. The main fault is about the breakdown in the elastic rubber coupling of the transmission system. It is found from the analysis of the real cases and data that the actual power consumption is increased and it is caused by the overload. The main parameters which influence the ball mill power consumption are load of the mill, feed material mass, ball mill rotational speed and friction. The main part of power consumption for ball mill is used to elevating grinding body and material, a portion is used to overcome the friction force between the main bearing. Under the conditions in which the load of the mill and feed material mass are kept the same, the parameters which influence the ball mill power consumption are rotational speed and friction status. When the ball mill voltage decreased, according to the motor characteristics, its rotation speed will decrease, which will disrupt the hydrodynamic lubrication state of the hollow shaft and spherical surface, so that the power consumption of the ball mill increase. The larger power leads to the transmission fault. This paper also put forward to make sure kept the ball mill main bearing lubrication status. DOI: http://dx.doi.org/10.11591/telkomnika.v11i4.2386